THE EFFECTS OF DIFFERENT DIETARY PROTEIN AND LIPID LEVELS AND OIL SOURCES ON THE GROWTH PERFORMANCE AND BODY COMPOSITION OF RAINBOW TROUT (ONCORHYNCHUS MYKISS,W.) - Bilguven, Murat; AK, Ibrahim (European Scientific Journal, ESJ, 2013)
In this research, the effects of different dietary protein and fat level, and various oil sources on the fattening performance and body carcass composition of rainbow trout (Oncorynchus mykiss) was investigated during 14 weeks. Throughout the feeding period, it was found that dietary protein and fat level had affected the average live weight, live weight gain, feed conversion ratio, protein efficiency ratio (PER), specific growth rate (SGR) and carcass composition significantly (P < 0,01), although they had not effected the condition factor and the ratio of internal organs weight to total body weight. Throughout the feeding period, it was determined that oil kinds had also affected the average live weight, live weight gain, feed conversion ratio, protein efficiency ratio (PER), specific growth rate (SGR) significantly (P < 0,01), while they hadn’t effected the carcass composition, condition factor and the ratio of internal organs weight to total body weight.